MASA DEPAN KOMUNIKASI: MENJELAJAH PERAN ARTIFICIAL INTELLIGENCE DALAM INTERAKSI MANUSIA - Pramana, Pramana; Utari, Prahastiwi; Alkhajar, Eka Nada Shofa; Widianti, Mira Adita (IAHN Gde Pudja Mataram, 2025)
The advancement of artificial intelligence (AI) has fundamentally transformed the way humans communicate. This study aims to explore the role of AI in interpersonal communication through a Systematic Literature Review (SLR) approach. By analyzing 44 relevant scholarly articles, this study identifies eight key themes: AI-mediated interpersonal communication, emotional impact, communication effectiveness and efficiency, access gaps and digital ethics, information validity, social trust, social representation and algorithmic bias, and projections of future communication. The findings indicate that AI can enhance communication efficiency and accessibility, yet poses risks of fostering pseudo-intimacy, reinforcing social bias, and diminishing the quality of interpersonal relationships if not ethically governed. The study underscores the importance of ethical-by-design principles, digital literacy, and regulatory frameworks that protect users from the misuse of AI-based communication systems. It advocates for an interdisciplinary and human-centered approach in the development of communication technologies to ensure that AI serves as a meaningful, inclusive, and responsible partner in human interaction. Accordingly, this research contributes conceptually to a deeper understanding of the future of communication situated at the intersection of technological advancement and human values